Crossing Miles viewing The Milestones: A Reflexive Inquiry into My Teaching Journey (The Batuk, 2019)
As a teacher involved in this profession for a decade and half I have had to deal with miscellaneous students from diverse backgrounds and having common and distinct individual and community needs. Basically, the paper to reflect different facets of my experience as a teacher regarding the cultural positionality and needs of the students. This paper attempts to explore how I have perceived, experienced and adopted/resisted culturally responsive pedagogy as a teacher. Threads of inquiry related to this paper are research/lecture based pedagogy, cultural integrity/transformation, local needs/ national priorities, teacher education, mentoring, monitoring and evaluation, decontextualization of curriculum and dis/respect to the students of different cultures. and 'Unpacking some facets of my professional molding' and 'Turning the lens towards myself' are the units under this paper. It is an auto/ethnographic study.